Radiographic study on premature loss of primary first molars leading to premature eruption of first permanent premolars - Sukmasari, Susi; Awang Nor, Norazizah; Sabri, Mohamad Yazid (Kulliyyah of Dentistry IIUM, 2011)
Objectives: Purpose of this study was to investigate racliographically the premature loss of primary first molars and thus consequence with the premature eruption of first permanent premolars among the paediatric patients. Materials and Method: A retrospective study on total 178 Orthopanthomograrns (OpGs) of 6-9 years old paediatric patients who attendecl to Students' poll'clinic, Kulliyyah of Dentistry, International Islamic Universiti Malaysia (Kuantan Campus) from January 2009 - April 2010. OPGs with missing and/or early eruption of Premolar were scrutinized to find out their relationship. X2 test and correlation "r" were used as significant tests for the study. Results: out of 178 OPGs, total 47 molar losses were observed in 32 OPG; total 21 premolar eruptions were also detected in 32 OPG. Prevalence of early loss of molar in the study was 29 early molar loss/ 1000 molar/ year. Prevalence of early eruption of premolar was l3 premolar/I000/ premolar/year. In the study ratio of early eruption of Premolar and early loss of molar was 1: 2.4; one premolar eruption was found out after 2.4 molar losses. There were no significant (p >0.05) between premature loss of prirnary first molars and the premature eruption of first permanent premolar, but some correlation (r:0.8) between number loss of molars and early eruption of premolars were observed. Conclusion: Orthopanthomogram radiograph are important diagnostic resources in developing dentition. It can be concluded that premature loss of primary first molars may lead to premature eruption of first permanent premolars.